Influence of the salaries of the academic personnel of the co-financed universities on the number of scientific publications - Juan Antonio Jimber del Rio; Argentina Arias Barrionuevo (Intangible Capital, 2025)
Purpose: The purpose of this paper is to examine the influence of the salaries of the academic staff of the co-financed universities of Ecuador on the number of scientific publications in Scopus, which is the indicator of research performance and quality. Design/methodology/approach: The paper uses a quantitative approach, using panel data analysis techniques, especially fixed-effects and random-effects models, to analyze the relationship between the salaries of the different academic career levels (graduate teaching assistants, adjunct instructors, and professors) and the number of publications in Scopus. The paper uses a log-log specification to ensure linearity in parameters and to facilitate interpretation. Findings: The paper finds that there is a significant positive relationship between the salaries of adjunct instructors and the number of publications. The paper also identifies the universities where each academic career level contributed the most to the growth of publications. Research limitations/implications: The paper has some limitations, such as the lack of data on other characteristics of the academic staff that may affect their research productivity, such as gender, age, work experience, teaching hours, or administrative duties. The paper also focuses on a specific set of co-financed universities in Ecuador during a given period, which may limit the generalization of the results to other universities or countries. Practical implications: The paper has some practical implications for policy makers and university administrators who are interested in improving the research performance and quality of the co-financed universities. The paper suggests that increasing academic salaries may not necessarily lead to higher scientific productivity, unless they are accompanied by other measures that enhance the quality and quantity of research inputs and outputs. For example, policy makers may consider providing more funding and support for research infrastructure, equipment, materials, training, dissemination, and collaboration. They may also design more effective incentive schemes that reward academic staff based on their research performance and impact, rather than their seniority or rank. Social implications: The paper has some social implications for society and academia. The paper shows that scientific production varies across different fields of study, departments, and schools of the co-financed universities. This may indicate that some fields have more resources, incentives, or opportunities for research than others. It may also reflect the different research cultures and expectations of each field. The paper also shows that scientific production contributes to the advancement of knowledge and innovation in various fields that are relevant for social and economic development, such as medicine, computer science, engineering, among others. Originality/value: The paper is original and valuable because there is a lack of literature that examines the influence of academic staff salaries on scientific production in co-financed universities in Ecuador. The paper uses panel data analysis techniques and econometric models to test the hypothesis that higher salaries lead to higher scientific productivity.